2021
DOI: 10.1001/jamanetworkopen.2021.27792
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Health Behavior Factors Associated With Clinical Trial Invitation and Participation in the United States

Abstract: IMPORTANCE Representative enrollment in clinical trials is critical to ensure equitable and effective translation of research to practice, yet disparities in clinical trial enrollment persist. OBJECTIVE To examine person-level factors associated with invitation to and participation in clinical trials. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study analyzed responses from 3689 US adults who participated in the nationally representative Health Information National Trends Survey, collected February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…The observational cohort showed a crossover rate of 23.6%, which is much lower than observed in this trial . Personal-level demographic and clinical characteristics have shown to play an important role in the decision to participate in clinical trials, and therefore, they are likely to differ between the trial and cohort population . Women without strong preconceived ideas on treatment choices may not only be more willing to be randomized, but they may also be more reluctant to continue allocated pessary therapy if subjective improvement would not meet their expectations.…”
Section: Discussionmentioning
confidence: 54%
“…The observational cohort showed a crossover rate of 23.6%, which is much lower than observed in this trial . Personal-level demographic and clinical characteristics have shown to play an important role in the decision to participate in clinical trials, and therefore, they are likely to differ between the trial and cohort population . Women without strong preconceived ideas on treatment choices may not only be more willing to be randomized, but they may also be more reluctant to continue allocated pessary therapy if subjective improvement would not meet their expectations.…”
Section: Discussionmentioning
confidence: 54%
“…The importance of research benefitting Black or African American people specifically has been expressed elsewhere as potentially motivating research participation (BeLue et al, 2006;Corbie-Smith et al, 1999;George et al, 2014;Herring et al, 2004;Iltis et al, 2021;Rogers et al, 2018;Williams et al, 2021). The expectation that research results will not benefit Black or African American people is a barrier to research participation in general (Corbie-Smith et al, 1999;Scharff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although patients may view the system (and the concept of clinical trials) as more tangential, prior studies have found that patients trust their own doctor's treatment decisions. 41,42 The clinician can play a major role in overcoming the low participation of Black patients by focusing on engaging in conversations surrounding risks and benefits of trial participation and offering trials to eligible patients. 43 This sentiment is supported both by our study results and the meta-analysis by Unger et al, 44 which demonstrated that when offered to participate, Black patients with cancer similarly enroll onto clinical trials when compared with White patients.…”
Section: Discussionmentioning
confidence: 99%